Graft copolymers of hydroxyethyl cellulose by a 'grafting to' method: 15N labelling as a powerful characterisation tool in 'click' polymer chemistry. Issue 9 (18th December 2014) - Joubert, Fanny; Musa, Osama; Hodgson, David R. W.; Cameron, Neil R.
Abstract : The use of 15 N labeling demonstrates the success of 'grafting to' preparation of cellulose graft copolymers by 'click' coupling. Abstract : We demonstrate how 15 N labelling can be used to probe the success of 'grafting to' processes, through the preparation of well-defined graft copolymers of hydroxyethyl cellulose by combining RAFT polymerisation and copper-catalysed azide-alkyne cycloaddition (CuAAC). Using synthesised alkyne-functionalised chain transfer agents, short-chain (DP = 10) poly( N -vinylpyrrolidone) (PVP) and poly( N -isopropyl acrylamide) (PNIPAAM) were prepared in high conversion in a controlled manner ( Đ M of ∼1.4 and 1.2 respectively). Separately, partially 15 N-labelled N3 -HEC was synthesised and characterised using solid state 13 C, 15 N CP-MAS NMR and FTIR spectroscopies. Alkyne-terminated PVP and PNIPAAM were grafted at different graft densities onto partially 15 N-labelled N3 -HEC using the click reaction. The hybrid HEC-g-polymer materials were fully characterised using solid state 13 C and 15 N CP-MAS NMR and FTIR spectroscopies. While 13 C and FTIR spectroscopies gave indirect or weak evidence of CuAAC coupling, the cycloaddition of the alkyne-terminated polymers with N3 -HEC was proven unambiguously by 15 N solid state NMR spectroscopy. This indicates the utility of 15 N labelling for probing the coupling efficiency of CuAAC reactions when employed in 'grafting to' processes with cellulosic substrates.